2016
DOI: 10.1186/s12943-016-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-505 functions as a tumor suppressor in endometrial cancer by targeting TGF-α

Abstract: BackgroundEndometrial carcinoma (EC) is one of the most lethal gynecologic cancers. Patients frequently have regional or distant metastasis at diagnosis. MicroRNAs are small non-coding RNAs that participate in numerous biological processes. Recent studies have demonstrated that miR-505 is associated with several types of cancer; however, the expression and function of miR-505 have not been investigated in EC.MethodsmiR-505 expression in normal endometrial tissue, endometrial carcinomas were quantified by Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 43 publications
3
70
1
Order By: Relevance
“…Since the miRNAs degrade in transiently transfected cells over time, 50 nM miRNAs are usually adopted as a working concentration, which can lead to an overexpression of the miRNA at the early stage after transfection. However, this method is well accepted by many researchers in miRNA study since it can detect miRNA function with more convenience and less expense434445. Here, we found that miR-27a up-regulation enhanced osteogenic differentiation and suppressed adipogenic differentiation by inhibiting PPARγ and GREM1 in steroid-induced rat BMSCs.…”
Section: Discussionmentioning
confidence: 69%
“…Since the miRNAs degrade in transiently transfected cells over time, 50 nM miRNAs are usually adopted as a working concentration, which can lead to an overexpression of the miRNA at the early stage after transfection. However, this method is well accepted by many researchers in miRNA study since it can detect miRNA function with more convenience and less expense434445. Here, we found that miR-27a up-regulation enhanced osteogenic differentiation and suppressed adipogenic differentiation by inhibiting PPARγ and GREM1 in steroid-induced rat BMSCs.…”
Section: Discussionmentioning
confidence: 69%
“…That might because the target genes of miR‐505 were largely involving in inhabitation of tumour progression and highly expressed miR‐505 could repress the expression of anti‐oncogenes resulting in the promotion of tumour. It has been reported that overexpression of miR‐505 could inhibit proliferation, induce apoptosis and reduce the tumorigenicity of endometrial cancer cells in vitro . Lu et al .…”
Section: Discussionmentioning
confidence: 99%
“…The kaleidoscopic biological functions of miRNAs are increasingly acknowledged in the development of various human diseases, among which miR‐505 was considered as a tumour suppressor in several malignancies. For example, it was confirmed that the tumour suppressor function of miR‐505 in endometrial cancer by targeting TGF‐α . In hepatoma cells, miR‐505 suppressed proliferation and invasion by directly targeting high‐mobility group box 1.…”
Section: Introductionmentioning
confidence: 92%